Evaluation of the Usability of Different Virtual Lab Software Used in Physics Courses - O. Karagoz; N. Ozdener (University of Sofia, 2010)
In recent years the use of virtual lab software has become ubiquitous in education settings. The purpose of the current study is to de¬velop an Evaluation Scale to allow the easy and fast assessment of virtual lab software. During the development of the Evaluation Scale, theoretical and experimental studies investigating the effects of different software on learn¬ing, particularly in terms of usability, were utilized. The Evaluation Scale was created by adding new attributes to pre-existing scales, and comprises three sections - attributes related to the interface of the software; attributes related to its use as a material in education; and attributes related to product and ser¬vice support - and 79 items. Testing of the Evaluation Scale was carried out using two different virtual lab programmes, with the help of a checklist. The evaluation was carried out by physics teachers and academics that had previ¬ously used similar software, and consistency between the results was consid¬ered to represent inter-rater reliability. At the end of the study, the usability of the Evaluation Scale was tested, and the instructor evaluations regarding the usability characteristics considered sufficient and that require improvement in virtual lab software were also investigated.